Quality assessment in family planning services in urban health centers affiliated to Shahid Beheshti University of Medical Sciences - Simbar M. (Payesh, 2007)
Objective (s): To assess the quality of family planning services in the urban health centers of Shahid Bchcshti University of Medical Science. Methods: This was a descriptive study to assess structure, process and outcome of the family planning care services. Fifteen health centers of Shahid Bcheshti University of Medical Science were randomized and the quality of care by sixty-five family planning care providers of these health centers were observed and assessed using checklists. Seventy-five clients were interviewed to assess their knowledge of their selected family planning method and to fill the satisfaction forms. Data collection tools were two observational checklists and two questionnaires. Data was analyzed using SPSS l I .5. Results: The study involved 75 clients with a mean age of24.7 (SD= 4), and 65 service providers, of whom 60 (92.3%) were midwives. The mean compatibility for the structure of family planning care service was 80.60 (±7.93) percent. General family planning care had 77.3 (±13.8) % compatibility with standards; the figure for specialized contraceptives was 57.5 (±17.4) %. The mean satisfaction rate was 83.3 (±9.05) %, while the mean knowledge score of clients concerning their method of choice was 59.1 (±18) %. Using Pearson correlation test, there were no significant correlations between clientschr('39') level of knowledge or their satisfaction with their demographic characteristics (P<0.05). Conclusion: The study of family planning services in the clinics run by Shahid Behesht University of Medical showed adequate facilities and sufficiently trained personnel: however, client knowledge concerning the selected contraceptive method was moderate. Therefore, there is a need for interventions to improve client counseling and education. This should be a major focus in the future research and planning efforts.